Tablet field data collection (shapefiles) - Vorster, Tony; Evangelista, Paul; West, Amanda; Young, Nicholas; Sturtevant, Robert; Mayer, Timothy; Woodward, Brian (Colorado State University. Libraries, 2017)
These shapefiles contain the 3,493 species occurrence and absence records for Russian olive and tamarisk represented in the Tablet Data Collection csv file. These are organized by location.
Data were collected in the field with high-resolution imagery loaded on computer tablets. Points were classified based on their dominant vegetation in three main categories: tamarisk, Russian olive, or absence. Dominance was defined as occupying greater than 50% of the canopy within a roughly 7 m radius circle. Collected information classified the status of tamarisk as either live, dead, a mixture of live and dead or having red foliage from tamarisk beetle attack (called "red phase tamarisk" in the data). Further, absence points were classified to indicate the dominant vegetation or land cover (i.e., water, bare ground, etc.) at that location.
The tamarisk & Russian olive data is mainly collected in Colorado, Utah and Arizona. Sampling is done opportunistically as land ownership, access, and logistics allow.
Users of these maps and other analysis products are solely responsible for interpretations made from these products. The Natural Resource Ecology Laboratory makes every effort to ensure this map is free of errors but does not warrant the map or its features are either spatially or temporally accurate or fit for a particular use. The Natural Resource Ecology Laboratory provides this map without any warranty, either express or implied.
Natural Resource Ecology Laboratory (NREL)
Keywords: field data; riparian vegetation; Invasive species